1976
DOI: 10.1080/00207547608956602
|View full text |Cite
|
Sign up to set email alerts
|

A learning curve prediction model for operators performing industrial bench assembly operations

Abstract: Learning curves of operators performing industrial operations vary according to the characteristics of the operator and the characteristics of the operation being performed.In this paper a method is developed to enable prediction of a specific learning curve of the function Y = c+ a( 1-exp -b(t -L)) for a. specific operator performing a specific operation. This specific curve is based on certain measurements of the operator and certain measurements of the operation. IntroductionLearning curves can be character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Bishu and Chen further concluded that greater performance improvements resulted from tasks performed in the order of difficult to easy than from those performed in the order of easy to difficult. Bohlen and Barany (1976) studied the direct effects of task complexity on learning parameters and concluded that task complexity affects The Effects of Task Complexity and Experience on Learning and Forgetting: A Field Study David A. Nembhard, University of Wisconsin-Madison, Madison, Wisconsin This paper examines the effects of task complexity and experience on parameters of individual learning and forgetting. Three attributes of task complexity and experience are addressed: the method, machine, and material employed.…”
Section: Introductionmentioning
confidence: 99%
“…Bishu and Chen further concluded that greater performance improvements resulted from tasks performed in the order of difficult to easy than from those performed in the order of easy to difficult. Bohlen and Barany (1976) studied the direct effects of task complexity on learning parameters and concluded that task complexity affects The Effects of Task Complexity and Experience on Learning and Forgetting: A Field Study David A. Nembhard, University of Wisconsin-Madison, Madison, Wisconsin This paper examines the effects of task complexity and experience on parameters of individual learning and forgetting. Three attributes of task complexity and experience are addressed: the method, machine, and material employed.…”
Section: Introductionmentioning
confidence: 99%
“…A;^(l -e-^'") (9) where vector p=[pc PD PLY and ß=[ßc ßö ßiY. Figure 2 shows the effect trend of each of the three factors (pc, Po, and pi) on the quality conforming rate when the other two factors are fixed.…”
Section: Operator's Experiencementioning
confidence: 97%
“…Traditionally, an operator's experience for performing a particular task refers to that operator's autonomous learning ability due to the repetitive execution of that task [9], While literature on learning curves abounds (e.g., Refs. [10,11]), there is limited research that addresses the effect of experience on quality conforming performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since pre-production preparation is prior experience, particularly if the construction of prototypes is part of the prior effort, the novelty hypothesis becomes further strengthened. Goldman and Hart (1965), Bohlen and Barany (1976) and Kvalseth (1978) have all established that task complexity influences the characteristics of the learning curve. In particular, the study by Kvalseth performed in a laboratory situation permitted an independent test of the effect of task complexity (entropy) on the parameters of the learning curve.…”
Section: Novelty and Rate Oj Progressmentioning
confidence: 97%